Association of dietary inflammatory index and dietary oxidative balance score with gastrointestinal cancers in NHANES 2005-2018 - Yu Chang; Chanjiao Yu; Xianyu Dai; Haibo Sun; Tongyu Tang (BMC, 2024)
Abstract Background&Aims Gastrointestinal (GI) cancers, including gastric, liver, esophageal, pancreatic, and colorectal cancers, represent significant global health burdens. Emerging evidence suggests that dietary patterns, particularly their inflammatory and oxidative properties, may influence cancer risk. The Dietary Inflammatory Index (DII) and Dietary Oxidative Balance Score (DOBS) assess the inflammatory and oxidative effects of diets, respectively. This study aims to explore the association between DII, DOBS, and the combined risk of GI cancers, and investigates the potential mediating roles of serum albumin and red cell distribution width (RDW). Methods Data from 26,320 participants in the NHANES 2005-2018 cycles were analyzed. DII was calculated based on 28 dietary components, and DOBS included 17 nutrients (3 pro-oxidants and 14 antioxidants). Logistic regression models assessed the associations between DII, DOBS, and GI cancers. Restricted cubic spline (RCS) models examined dose-response relationships. Mediation analysis evaluated the roles of serum albumin and RDW. Subgroup analyses explored interactions with demographic and health-related factors. Results Higher DII was associated with increased GI cancer risk (OR: 1.26, 95% CI: 1.07-1.49 per unit increase), while higher DOBS was associated with reduced risk (OR: 0.90, 95% CI: 0.76-0.99 per unit increase). RCS analysis indicated a significant nonlinear relationship between DII and GI cancer risk. Serum albumin and RDW partially mediated the associations between DII, DOBS, and GI cancers. Subgroup analyses showed stronger associations for DII among certain demographics, and significant interactions were found between DII and BMI. For DOBS, significant interactions were observed with age and BMI. Conclusion This study reveals significant associations between dietary inflammatory and oxidative balance scores and GI cancer risk. Higher DII is linked to increased risk, while higher DOBS is protective. The mediating roles of serum albumin and RDW provide insights into underlying mechanisms. These findings underscore the potential of dietary modifications in GI cancer prevention and management, emphasizing the importance of anti-inflammatory and antioxidant-rich diets.